To calculate the average rate of change over the interval [−2,−1], we need to substitute the values for f(b) and f(a) into the provided formula:
f(b) - f(a) / b - a
In this case, b = -1 and a = -2, so the formula becomes:
(3 - 1) / (-1 - (-2))
Simplifying:
(3 - 1) / (-1 + 2)
= 2 / 1
= 2
Therefore, the average rate of change over the interval [−2,−1] for the function y = 3x + 2 is 2.
Use the formula f(b)−f(a)b−a to calculate the average rate of change over the interval [−2,−1] given the function table for y=3x+2 . Express your answer as an integer. x f(x) −3 13 −2 1 −1 3 0 9(1 point) The average rate of change is
1 answer